(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Two compounds, ergosterol (1) and 4-hydroxy-hexadec-6-enoic acid methyl ester (2) were isolated from the ethyl acetate extract of the endophytic fungal strain labeled as MI-3, isolated from the leave of Magnifera indica L. The structures of the isolated compounds were elucidated by 1H NMR studies and comparing with published data. The crude ethyl acetate extract, three column fractions and ergosterol were tested for antimicrobial activity against five Gram-positive and eight Gram-negative bacteria and three fungi by disc diffusion method. The general toxicity and antioxidant activity of the parent extract, column fractions and ergosterol were also evaluated by using brine shrimp lethality assay and free radical scavenging assay, respectively. Low activities were observed in all cases. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21862 Dhaka Univ. J. Pharm. Sci. 13(1): 63-67, 2014 (June)